Inclusive search for highly boosted Higgs bosons decaying to bottom quark-antiquark pairs in proton-proton collisions at root s=13 TeV - Sirunyan, A. M. (2020)
A search for standard model Higgs bosons (H) produced with transverse momentum (p(T)) greater than 450 GeV and decaying to bottom quark-antiquark pairs (b (b) over bar) is performed using proton-proton collision data collected by the CMS experiment at the LHC at root s = 13 TeV. The data sample corresponds to an integrated luminosity of 137 fb(-1). The search is inclusive in the Higgs boson production mode. Highly Lorentz-boosted Higgs bosons decaying to b (b) over bar are reconstructed as single large-radius jets, and are identified using jet substructure and a dedicated b tagging technique based on a deep neural network. The method is validated with Z -> b (b) over bar decays. For a Higgs boson mass of 125 GeV, an excess of events above the background assuming no Higgs boson production is observed with a local significance of 2.5 standard deviations (sigma), while the expectation is 0.7. The corresponding signal strength and local significance with respect to the standard model expectation are mu(H) = 3.7 +/- 1.2(stat)(-0.7)(+0.8)(syst)(-0.5)(+0.8)(theo) and 1.9 sigma. Additionally, an unfolded differential cross section as a function of Higgs boson p(T) for the gluon fusion production mode is presented, assuming the other production modes occur at the expected rates.